(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2013)
We have designed an improved iron determination method based on the ability of ferrous iron to reduce 12-molybdophosphate (12-MP). The method allows for direct determination of ferrous iron in the presence of azo dyes. The iron determination method had a specific extinction coefficient of 0.0514 (mg l-)-1.cm-1 at 865 nm with a correlation coefficient of 0.999. The relative standard deviation for each data point does not exceed 5% (n=3) suggesting precision. In its oxidized state 12-MP is yellowish in color and when reduced it forms a blue solution. The iron determination method is less interfered with azo dyes compared to common iron determination methods such as 1,10-phenanthroline and the commercial FerreMoTM.